UMP excels in ITEX 2022, brings home 14 gold, 10 silver for innovative research products - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2022)
KUANTAN: An innovation to boost the extraction of agarwood oil was among the outstanding products which saw Universiti Malaysia Pahang(UMP) walk away with 14 gold medals at the International Invention, Innovation and Technology Exhibition (ITEX) 2022 held at the Kuala Lumpur Convention Centre recently.